Overview of Community Knowledge about the Dagusibu of Antibiotics - Anggraini, Truly; Angelica, Jessika Shallom (Indonesian Journal of Global Health Research, 2024)
The Antimicrobial Resistance Control Committee explains that the rate of bacterial resistance in Indonesia has continued to increase from 40% in 2013 to 60.4% in 2019. One of the causes of antibiotic resistance is the lack of information regarding antibiotic knowledge among the general public. Preliminary study results show that the community knowledge in Banjaran Hamlet about the use of antibiotics is still low at 40%. The Indonesian Pharmacists Association created the health education program DAGUSIBU (Get, Use, Store, Dispose) as part of the Family Medicine Awareness Movement to improve the quality of life for the community. This study aims to determine the level of community knowledge about DAGUSIBU antibiotics in Banjaran Hamlet, Wonosari District, Klaten Regency. The method used in this study is descriptive quantitative, utilizing a questionnaire to assess community knowledge about DAGUSIBU antibiotics. The sample size was calculated using the Slovin formula, resulting in a sample of 190 respondents. The study results in Banjaran Hamlet showed that 71.58% fell into the good knowledge category, while 28.42% fell into the poor knowledge category. The results of this study are expected to help the community improve their knowledge about the proper use of DAGUSIBU antibiotics.